2009
DOI: 10.1016/j.nucengdes.2009.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the characteristics of the flow in the first rows of tube banks

Abstract: In the present work, the flow through tube banks is studied in order to understand the random and transient behavior of the instabilities and phenomena that occur in the first rows of tube banks and propagates to its interior. The study is performed using hot wire anemometry in an aerodynamic channel and flow visualizations in a water channel. Three tube banks with square arrangement and pitch-to-diameter ratios of 1.26, 1.4 and 1.6 were studied. The Reynolds number range for the velocities measurements, compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
(7 reference statements)
1
15
0
1
Order By: Relevance
“…It is possible that flow instability was occurring at those velocities but it was not as pronounced as in the other cases and was masked by turbulence. Olinto et al (2009) reported that the bi-modal jet switching did not occur in water flow, but did in air flows at the same Reynolds number, but at higher flow velocity. So, an alternative explanation for an absence of jet switching at low velocities in this study, might be that there is some minimum flow velocity (i.e.…”
Section: Pressure Distributionmentioning
confidence: 97%
“…It is possible that flow instability was occurring at those velocities but it was not as pronounced as in the other cases and was masked by turbulence. Olinto et al (2009) reported that the bi-modal jet switching did not occur in water flow, but did in air flows at the same Reynolds number, but at higher flow velocity. So, an alternative explanation for an absence of jet switching at low velocities in this study, might be that there is some minimum flow velocity (i.e.…”
Section: Pressure Distributionmentioning
confidence: 97%
“…Olinto et al (2006) determined by means of wavelet analysis of the results of hot wire experiments the presence of a biased and bistable flow mode in in-line tube banks and compared to the flow on two cylinders placed side-by-side. Further measurements together with flow visualizations in a water channel identified a phenomenon of random change in the flow mode, characterized by the presence of transversal components to the main flow that lead to the generation of a three dimensional behavior similar to the bistable flow that occurs in the flow on two tubes placed side by side, with the same scale to that of the channel (Olinto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Wavelet analysis is a useful tool for the study of transient turbulent signals (Indrusiak et al, 2005;Olinto et al, 2009), and especially for the switching phenomenon in two side-by-side cylinders (Alam et al, 2003;Alam and Sakamoto, 2005). The use of wavelets together with flow visualizations can enhance the study of fluid flow phenomena in laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…W zależności od wielkości strumieni doprowadzanych faz, ich właściwości fizykochemicznych i(lub) parametrów wrzenia formują się różne struktury przepływu. Duża liczba nowo wydawanych publikacji z tego zakresu pokazuje, że badania przepływu dwufazowego są wciąż w kręgu zainteresowań badaczy [2][3][4]. Jest to również spowodowane faktem, że pomimo wielu badań nad strukturami przepływu dwufazowego ich charakter nie został jeszcze w pełni poznany.…”
Section: Wstępunclassified